Form of Language Errors in The Syntastic Order When the Essay Writing Process Personal Experience - Vivi Novalia Sitinjak; Putri Yustika Tambunan; Ruth Friska Silitonga; Sepriyumi Rumondang Tamba (Linguistic, English Education and Art (LEEA) Journal, 2023)
This study aims to describe errors at the syntactic level which include aspects of phrases and sentences in writing personal experiences. This study used a qualitative research design with a descriptive research type. The results of this study indicate that students make many mistakes in sentence structure which includes ten aspects. These findings prove that students pay little attention to the use of grammar in writing, the lack of vocabulary that students have, the influence of the use of regional languages, and the teacher pays little attention to the use of grammar in writing. The method used in this research is descriptive qualitative method. Based on the results of the research, the researchers found data on language errors in the syntactical aspect, including: 8 errors in the word aspect, 1 error in the phrase aspect, and 34 errors in the sentence aspect. From the findings of these data researchers chose 3 data to be analyzed. These data are: 1 word aspect error, 1 phrase aspect error, and 1 sentence aspect error. Keywords: Language, Sentence, Syntastic